Partial plan based on the conservation of green areas and water bodies for the citadel "Peñón del Rio", Canton Durán Ecuador. - Viteri, Jose Luis (Artes: Architecture, Technology and Sustainability, 2022)
The Durán canton presents an accelerated growth of urban population which has generated the loss of natural habitats causing it to lack recreational and green areas where leisure activities can be developed; therefore, one of the areas that have more spaces available for the development of different proposals, is the citadel "Peñón del Río", which has vegetation cover. The objective of this study is to develop a Partial Land Use Management Plan based on the conservation of green areas and water bodies, containing a sustainable housing proposal and recreational areas with urban design strategies for environmental preservation. The analysis methodology that was used is field observation which allowed the identification of various plant species and urban characteristics of the study area, in addition to the zoning of the use of land for the conservation of green areas, water bodies, and recreational areas for the best use of space. On the other hand, a survey of citizens was carried out to determine the determination that merited the implementation of sports zones and recreational areas. Additionally, sustainable urban design strategies were established for housing development. As a result, a proposal is proposed where the inclusion of green areas in territorial planning, their friendly interaction with the population, and strategies for a sustainable project stand out. In conclusion, the data demonstrates the need for the sector and the population to have natural spaces that favor improving living conditions.